Agrotourism Development Strategy Parak Kafe Orange Orchard DT. Timbijo in Nagari Koto Laweh, X Koto District, Tanah Datar Regency (Sumatra Journal of Disaster, Geography and Geography Education, 2023)
The purpose of this study is to study the development strategy of the Orange Garden Café Parak Dt. Timbijo in Nagari Koto Laweh, Tanah Datar Regency. This research method uses SWOT analysis, namely by developing conditions and evaluating a problem and projecting it into an applicable business concept. Researchers also conduct comprehensive and focused research to obtain complete and detailed data about those studied through observation and direct fieldwork. Parak Orange Garden Café is located in the middle of Koto Laweh Nagari whose position is not difficult to access. Parak Tourism Cafe Kebun Jeruk dt. Timbijo can generate income for its owner. To enter Parak Agrotourism Cafe Kebun Jeruk Dt. Timbijo tourists do not need to pay for entrance tickets, it's just that they are required to order the existing menu. If tourists want to bring home citrus fruits can buy directly at the orange plantation at a price of Rp 2 5,000 per kilo can be picked alone or assisted by employees at Parak Café. Agrotourism Parak Kafe Kebun Jeruk Dt. Timbijo in its development has not been able to fully cooperate with the Nagari government and the local community so in its control assisted by the presence of competent human resources. From Parak café, it can be found that there are 13 strategies that need to be developed in Parak Agrotourism, Orange Garden Cafe, Dt. Timbijo, then it is also necessary that promotional activities can be done through social networks to spread the news of other passengers and can be added to the existing facilities and infrastructure in Parak Agrotourism, Orange Garden Cafe, Dt. Timbijo.